2008
DOI: 10.1016/j.mce.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin, a regulatory partner of the estrogen receptor alpha in breast cancer cells

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 73 publications
5
28
0
1
Order By: Relevance
“…Numerous differentially regulated genes have been implicated in ER-mediated actions (functional theme E in Tables 2 and 3), which are typified by calmodulin (18,30), hsp90b (10,29), O-GlcNAc transferase (7), UCE2 variant 1 (39,59), and the dynein light chain (22,48). The expression change of calmodulin was verified by real-time PCR in the current study.…”
Section: Discussionsupporting
confidence: 61%
“…Numerous differentially regulated genes have been implicated in ER-mediated actions (functional theme E in Tables 2 and 3), which are typified by calmodulin (18,30), hsp90b (10,29), O-GlcNAc transferase (7), UCE2 variant 1 (39,59), and the dynein light chain (22,48). The expression change of calmodulin was verified by real-time PCR in the current study.…”
Section: Discussionsupporting
confidence: 61%
“…As such, these proteins might have the potential to be putative breast cancer markers. As expected, some well-known breast cancer markers, such as 14-3-3 proteins (Danes et al, 2008), annexins (Cao et al, 2008a), calmodulin (Gallo et al, 2008), anterior gradient homolog 2 (AGR-2) (Zweitzig et al, 2007;Fritzsche et al, 2006), Galectin-1 (Jung et al, 2007) and Rho-associated protein kinase-2 (ROCK2) (Fu et al, 2008b), were also identified in this 2D-DIGE experiment, lending credence to the reliability of early phase biomarker detection using this experimental strategy. Fig.…”
Section: D-dige and Maldi-tof Ms Analysis Of Total Intracellular Prosupporting
confidence: 79%
“…Cytosolic and nuclear Ca 2ϩ levels serve as a second messenger in the cell (41, 42) that controls biosynthesis and/or signaling of E2 (43). Our model illustrates how ER-␣ might integrate estrogen signals and calcium cascades during signal transduction to control gene expression in neurons (44) and breast cancer cells (11). The mechanism in Fig.…”
Section: Discussionmentioning
confidence: 90%